Mentalizing in psychodynamic and psychoanalytic psychotherapy: basics, applications, case studies - Brockmann, Josef; Kirsch, Holger; Taubner, Svenja (Routledge, 2025)
Characteristics of a Modern Psychotherapy -- Central Aspects of the Mentalizing Concept -- Mentalization-Based Therapy (MBT) -- Psychoanalysis and Mentalization -- Mentalization in Psychodynamic and Psychoanalytic Psychotherapy -- Case Studies -- Take Home Message.